I-shaped ECC/UHPC composite beams reinforced with steel bars and BFRP sheets - Dong, Zhiqiang; Ji, Jianghao; Liu, Ziqing; Wu, Chang; Wu, Gang; Zhu, Hong; Zhang, Pu (Sustainable structures, 2023)
This paper proposes a new type of small-sized I-shaped engineered cementitious composite (ECC)/ ultra-high performance concrete (UHPC) composite beam which has the potential to be suitable for corrosive environments. The lower tensile part of the beam was made of ECC material (2/3 of the height), and the top compressive part was made of UHPC material (1/3 of the height). Inner embedded steel bars and surface-bonded basalt fiber reinforced polymer (BFRP) sheets were adopted as the reinforcing materials in combination. A total of nine I-shaped beams were designed and tested under four-point bending test. The influence of parameters such as the ratio of the embedded tensile steel bars, the top UHPC flange, and the surface bonded tensile BFRP sheet on the behavior of the beams was investigated. The results showed that the I-shaped ECC/UHPC composite beams have excellent comprehensive performance, and thanks to the ultra-high durability of the component materials, they have ultra-high durability that ordinary I-steel beams do not have and thus have broad application prospects in corrosive environments. The shear resistance capacity of the thin-walled ECC web needs to be further improved, and UHPC is recommended for the web in the follow-up study.